Update on osteonecrosis related to bisphosphonates: A report of three clinical cases - NEHMÉ, Edgard; KHOUEIR, Nadim; HOYEK GEBEILY, Jeanine (International Arab Journal of Dentistry (IAJD), 2012)
The publications issued since 2003 on osteonecrosis related to oral and / or iv bisphosphonates (BsP) lend a controversy. The recommendations and guidelines from senior scientific authorities reviewed and updated in 2009 by the task force of the AAOMS, define patients in terms of risk and determine practically the prophylactic acts and the limits of operative oral and dental procedures. In these serial clinical cases, we report and discuss three situations with different therapeutic approaches and management.